Pengujian Power 5 Volt Di Laboratorium Teknik Elektronika Politeknik Negeri Malang - Imam Saukani (Integrated Lab Journal, 2020)
Power supplies are generally used to supply electronic devices that require DC current (Enny, 2016). The use of a power supply in a practicum with the material "Transistor Characteristics" in an analog electronics laboratory requires 3 voltage variations (5,9,12 volts) simultaneously, meaning that if one class is divided into 5 groups, 15 power supplies are used, while the availability is limited. This research aims to determine the voltage divider method, the resistance value and to analyze the responsible voltage for the change in resistance.Variable resistance to change the output voltage value of the Integrated Circuit (IC) regulator to produce a voltage of 5,9,12 volts. The change in output voltage will be analyzed against changes in resistance. The ripple voltage limit is 2%, so a filter is needed. The output current from the regulator IC is in the order of milli amperes, so it needs to be strengthened to 1 ampere to be used in a practicum with the theme "Transistor Characteristics".It is expected that the results of this study are to improve the performance of a 5 volt power supply having a voltage output of 5,9,12 volts simultaneously, so that the need for power supply for the “Transistor Characteristics” practicum which initially requires 15 to 5.